Teste das microbolhas estáveis no diagnóstico precoce da síndrome do desconforto respiratório do recém-nascido - Herazo, Alonso Acevedo (2022)
Introduction: Respiratory Distress Syndrome (RDS) in newborns (NB) is caused by alveolar surfactant deficiency, which makes gas exchange in the lungs difficult, leading to respiratory distress (RD). The stable microbubble test (TME) is a diagnostic method of the disease, which quantifies the activity and presence of surfactant in the lung, helping the early administration of the surfactant. Objective: To analyze the importance of TME in the early diagnosis of RDS in newborns with gestational age between 32 and 37 weeks with respiratory distress. Methodology: Observational, descriptive, prospective study. It consisted of newborns with gestational age between 32 and 37 weeks, with and without SDR. The collection took place at the University Hospital of Santa Maria - HUSM, Between March 2018 and February 2020 Results: The groups of patients with and without respiratory distress were compared in relation to the number of stable microbubbles. Among the NB with RD, 6 (50%) had between 15 and 50 mbe/mm² and 6 (50%) > 50 mbe/mm². In patients without RD, 2 (18%) newborns had between 15 and 50 mbe/mm², while 9 (82%) had > 50 mbe/mm², with no significant difference. Mothers of newborns with RD received prepartum corticotherapy, a protective factor for the development of SDRRN, not requiring the use of exogenous surfactant. Conclusion: using TME to aid in the diagnosis of SDRRN was a good method, as no NB required exogenous surfactant, and there were no NB with < 15 mbe/mm² in this small group of patients. Certainly, an amount greater than 15 mbe/mm² in NBs with respiratory distress indicates non-moderate or severe RDS, which does not require exogenous surfactant.